Sodium Zirconium Cyclosilicate Compared with Polystyrene Sulfonate for the Management of Hyperkalemia in Chronic Kidney Disease: A Systematic Review - Bella Yanita; Januar Ishak Hutasoit (Jurnal Sehat Indonesia (JUSINDO), 2026)
Background: Hyperkalemia is a common and potentially life-threatening complication in patients with chronic kidney disease (CKD). Methods: This systematic review followed the PRISMA 2020 guidelines. A comprehensive literature search was conducted using PubMed, ScienceDirect, and the Cochrane Library to identify randomized controlled trials and comparative observational studies involving adult patients with CKD and hyperkalemia. Studies comparing sodium zirconium cyclosilicate (SZC) with polystyrene sulfonate–based binders and reporting efficacy or safety outcomes were included. Data extraction and risk of bias assessment were performed, and a qualitative synthesis of results was conducted due to study heterogeneity. Results: Eight studies were included in the qualitative analysis, comprising seven interventional and hospital-based observational studies involving 690 patients and one large nationwide cohort including more than 70,000 patients. In acute settings, SZC achieved rapid reductions in serum potassium, with greater or comparable efficacy to polystyrene sulfonate–based binders. In chronic management, SZC was associated with earlier normalization and more sustained potassium control. Safety outcomes were generally comparable, with favorable tolerability and patient preference observed for SZC. Discussion: The included studies consistently demonstrated effective potassium lowering with SZC across acute and chronic settings. While heterogeneity and the predominance of observational data limit causal inference, the overall findings support the clinical utility of SZC, particularly in facilitating long-term potassium control and treatment adherence. Conclusion: SZC represents an effective and well-tolerated alternative to polystyrene sulfonate–based binders for the management of hyperkalemia in patients with CKD. Further well-designed randomized studies are warranted to confirm long-term clinical benefits.